Economic impact of childhood psychiatric disorder on public sector services in Britain: estimates from national survey data. (27th February 2013) - Snell, Tom; Knapp, Martin; Healey, Andrew; Guglani, Sacha; Evans‐Lacko, Sara; Fernandez, Jose‐Luis; Meltzer, Howard; Ford, Tamsin
<x xml:space="preserve">Abstract</x> Background Approximately one in ten children aged 5–15 in Britain has a conduct, hyperactivity or emotional disorder. Methods The British Child and Adolescent Mental Health Surveys (BCAMHS) identified children aged 5–15 with a psychiatric disorder, and their use of health, education and social care services. Service costs were estimated for each child and weighted to estimate the overall economic impact at national level. Results Additional health, social care and education costs associated with child psychiatric disorders totalled £1.47bn in 2008. The lion's share of the costs falls to frontline education and special education services. Conclusions There are huge costs to the public sector associated with child psychiatric disorder, particularly the education system. There is a pressing need to explore ways to reduce these costs while improving health and well‐being.